Peran Tradisi Wetonan dalam Menjaga Identitas Budaya Masyarakat Adat Jawa - Saffana Alzahra; Desy Safitri; Sujarwo (PT. PENERBIT TIGA MUTIARA, 2024)
The wetonan tradition is a birth calculation system based on the Javanese calendar, a cultural heritage of the Javanese indigenous people that is rich in spiritual values and local wisdom. In this context, the wetonan tradition is not only a series of ceremonies or astrological calculations, but also a cultural heritage that includes local wisdom values and spiritual beliefs that have been passed down from generation to generation. In the current era of globalization, the wetonan tradition is faced with various challenges that threaten its survival. Changes in people’s attitudes and mindsets, urbanization, and doubts about traditional values are some of the main challenges. Shifting values and priorities in society, changes in value and belief systems, and doubts about the role of tradition in the era of globalization are some of the main challenges. However, preserving the wetonan tradition is crucial to maintaining a rich and diverse cultural identity and strengthening the solidarity of Javanese indigenous communities. To maintain and face the challenges of the wetonan tradition remaining relevant and valued by the community, concrete steps are needed. In facing this challenge, it is important to continue to educate the public about the cultural and spiritual values contained in the wetonan tradition, as well as to replant these values to strengthen the sustainability of the wetonan tradition amid the ongoing flow of modernization and globalization. Thus, the wetonan tradition can continue to live and develop as an integral part of the cultural identity of Javanese society. The preservation of this tradition not only ensures the continuity of a rich cultural heritage, but also strengthens solidarity and togetherness in Javanese indigenous communities. Therefore, measures to maintain and preserve the wetonan tradition need to be continuously strengthened to ensure that this cultural heritage remains alive and relevant for future generations.